Integrative muscle-adipose score (IMAS) predicts sex-specific long-term survival after orthotropic liver transplantation - Schliephake, Frederik; Lurje, Isabella; Dreher, K.; Bitar, J.; Jiang, D.; Bednarsch, J.; Czigány, Zoltán; Schneider, C.; Strnad, P.; Engelmann, C.; Tacke, F.; Neumann, U. P.; et al. (Zeitschrift für Gastroenterologie, 2025)
Background and aims: Body composition reflects nutritional status and metabolic reserves and predicts the outcome of orthotopic liver transplantation (OLT). Given the increasing evidence of sex-specific disparities in OLT outcomes, body composition scores that are equally predictive in both sexes are urgently needed. Therefore, we investigated the interplay between muscle and fat composition as well as gender in a multicentric European cohort of patients undergoing OLT. Methods: 697 patients undergoing OLT at the Charit & eacute; - Universit & auml;tsmedizin Berlin (n=414, 2010-2020, discovery cohort) and the University Hospital RWTH Aachen (n=283, 2010-2018, validation cohort) were included. The median follow up duration was 51 months. CT-based body composition was assessed at lumbar level 3/4. The parameters skeletal muscle mass, muscle composition, and visceral and subcutaneous fat quantity were combined into an Integrative Muscle-Adipose-Score (IMAS) and correlated with patient outcomes in univariable and multivariable regression analyses. Survival was reported with 95% Confidence intervals (CI) and Hazard ratios (HR). Unisex Cutoffs were derived via ROC analysis and Youden-Index. The sex specific performance of IMAS was compared to the Balance of Risk score (BAR) in male and female cohorts pooled from both centers ( Fig. 123 ). Results: Recipient and donor ages were 57 +/- 10.9 and 58 +/- 16.5 years in the Berlin cohort, and 55 +/- 11.3 and 56 +/- 15.8 years in the Aachen cohort, respectively. 215 (31%) patients were female. IMAS quartiles successfully stratified overall survival (OS) in both the Berlin (p=0.003) and Aachen (p=0.016) cohorts. Patients with a low IMAS had significantly reduced OS (Berlin: 83.4 vs. 97.7 months p=0.009; Aachen: 57.4 months vs. 68 months; p0.021). The results remained significant in a multivariable analysis. While the BAR-Score failed to predict OS in female patients, sex-specific IMAS Cut-offs were independently prognostic of OS in both sexes (male: HR 1.743, CI: (1.238 - 2.456); p<0.001; female: HR 1.921 (CI: 1.062 - 3.477); p=0.031). Low IMAS was associated with significantly lower OS in male (78.7 vs. 100.4 months; p<0.001) and female (87.5 vs. 106.9 months; p=0.022) patients. Conclusion : The integration of key metabolic body compartments into a unified index is a novel tool for sex-specific risk assessment of long-term patient survival after OLT.